Wall photography What Remains - An incursion into the surface of urban murals of Bucharest city center - Irian, Ana Cristina (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
The idea of studying city walls as both a form of urban skin in constant change and archives of recent memory has come from questions related to what remains of the decomposing process of walls' surfaces used as communication tool, to how do walls react to people affixing/drawing actions, to what are the new aesthetic elements that arise from the interaction people-walls in urban environments. The analysis is structured along four main lines: 1) the sources of original images affixed; 2) the process of new images creation; 3) the type of images shaped and 4) the way materials mix. The following artists conducted connected photographic research: G. Brassai· (surface of derelict industrial places), Sally Mann ('What remains' - human bodies), Ernst Haas (urban ripped posters) and Walker Evans (movie ripped posters). Connected graffiti archeological research is conducted by the group guided by Cassidy Curtis on http:/Igrafarc.org/about.html